2014
DOI: 10.1002/jbm.a.35138
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of electrospun curcumin loaded poly(2-hydroxyethyl methacrylate) nanofiber-A biomaterial for multidrug resistant organisms

Abstract: Curcumin loaded poly(2-hydroxy ethyl methacrylate) p(HEMA) nanofiber were produced using electrospinning method and characterized. The nanofibrous scaffold supports good cell growth, attachment and retains its original morphology. Sustained and controlled release pattern of curcumin seen to be efficient against infectious disease caused by multidrug resistant organisms. Antibacterial activity of curcumin against Methicillin resistant staphylococcus aureus (MRSA) and extended spectrum β lactamase (ESBL) proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…Relatively high amounts of curcumin have been incorporated in electrospun materials, as most of the studies carried out propose proportions of curcumin 1% of the polymer weight. [19][20][21][22]25,28 These materials often lead to concentrations near or above the apoptosis threshold of 10 μM. Although several authors claim benefits from such materials to stimulate repair, it is not clear why these amounts have been selected while data from studies carried out with free curcumin suggest that lower concentrations might be more adequate for wound healing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively high amounts of curcumin have been incorporated in electrospun materials, as most of the studies carried out propose proportions of curcumin 1% of the polymer weight. [19][20][21][22]25,28 These materials often lead to concentrations near or above the apoptosis threshold of 10 μM. Although several authors claim benefits from such materials to stimulate repair, it is not clear why these amounts have been selected while data from studies carried out with free curcumin suggest that lower concentrations might be more adequate for wound healing applications.…”
Section: Introductionmentioning
confidence: 99%
“…The formed formazan crystals were then dissolved by adding 100 µL of DMSO and this was mixed properly by pipetting up and down. Spectrophotometrical absorbance of the purple blue formazan dye was measured in a microplate reader at 570 nm (Biorad 680) [20,29]. Cytotoxicity was determined using Graph pad prism 6 software.…”
Section: Isolation Of Hap From Chicken Bonementioning
confidence: 99%
“…Ramalingam et al used electrospinning method to produce poly (2-hydroxyethyl methacrylate) p(HEMA) nanofibers containing different concentrations of curcumin. They reported that these nanofibers had high antibacterial activity against E. coli and S. aureus bacteria [7]. In another study, functionalized PCL/PVP nanofibers were produced by the electrospinning method by combining Tecomell undulata plant extracts which have therapeutic property for wound healing against typical hospital pathogens of P. aeruginosa, S. aureus, and E. coli [8].…”
Section: Introductionmentioning
confidence: 99%